Non‐surgical prevention and management of scoliosis for children with Duchenne muscular dystrophy: What is the evidence?. (7th April 2013) - Harvey, Adrienne; Baker, Louise; Williams, Katrina
<x xml:space="preserve">Abstract</x> A review was performed to examine the evidence for non‐surgical interventions for preventing scoliosis and the need for scoliosis surgery in children with Duchenne muscular dystrophy. Medline and Embase databases and reference lists from key articles were searched. After the inclusion and exclusion criteria were applied, 13 studies were critically appraised independently by two reviewers. The included studies examined spinal orthoses and steroid therapy. There were no studies with high levels of evidence (randomised or other controlled trials). The studies with the highest level of evidence were non‐randomised experimental trials. There is some evidence that children with Duchenne muscular dystrophy who receive steroid therapy might have delayed onset of scoliosis, but more evidence is required about the long‐term risks versus benefits of this intervention. There is weak evidence that spinal orthoses do not prevent and only minimally delay the onset of scoliosis.